1990
DOI: 10.1034/j.1399-3054.1990.790212.x
|View full text |Cite
|
Sign up to set email alerts
|

Polysome formation and incorporation of new ribosomes into polysomes during germination of the embryonic axis of maize

Abstract: Dommes, J. & Van de Walle, C. 1990. Polysome formation and incorporation of new ribosomes into poiysomes during germination of the embryonic axis of maize. P hysioi. Plant. 79: 289-296.Isolated axes of Zea mays L. cvs CiVj and CUZCO were imbibed for different periods of time, and free poiysomes were extracted and ,analysed by centrifugation in a sucrose gradient. The amount of rRNA per axis was determined at different moments of germination. Polysome reassembly was practically completed by 8 h and 54% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…The majority of the 1,251 proteins examined in germinating Arabidopsis embryos by Gallardo et al (2001) were also found in the dormant embryo. It is also recognised that the translation machinery reforms rapidly following imbibition (Dommes and Van der Walles 1990). Here the observed increase in accumulation prior to and during germination of transcripts encoding translation activation factors supports this concept.…”
Section: Changes In Accumulation Of Mrnas Encoding Proteins Involved supporting
confidence: 69%
“…The majority of the 1,251 proteins examined in germinating Arabidopsis embryos by Gallardo et al (2001) were also found in the dormant embryo. It is also recognised that the translation machinery reforms rapidly following imbibition (Dommes and Van der Walles 1990). Here the observed increase in accumulation prior to and during germination of transcripts encoding translation activation factors supports this concept.…”
Section: Changes In Accumulation Of Mrnas Encoding Proteins Involved supporting
confidence: 69%
“…In our studies we applied a short 30 rain incubation of seedling with labelled amino acids. In such conditions the vast majority of polysome-associated label is in nascent protein (Dommes and Van de Walle 1990;You et al 1992). …”
Section: Discussionmentioning
confidence: 96%
“…TopHat2 (version 2.0.10) was used to align reads to the V1 version of the PN40024 Vitis vinifera reference genome annotation obtained at EnsemblPlants [ 99 ]. Filtered reads were aligned with the “--b2-very-sensitive” option for Tophat2 and “--transcriptome-index” option with a corresponding EnsemblPlants-sourced index, as in [ 33 , 100 ]. Remaining parameters were kept at default.…”
Section: Methodsmentioning
confidence: 99%